EFEKTIVITAS PENGGUNAAN APLIKASI RUANG GURU PADA SISWA SEKOLAH DASAR KELAS VI DALAM PENINGKATAN KULITAS PENDIDIKAN DI KOTA MAKASSAR - Yulianti Retno Wulandari; Kaharuddin; Ashar Ashar (Nusantara Hasana Berdikari, 2022)
This study aims to describe how effective the use of the teacher's room application is in improving the quality of education in Makassar City. This research includes qualitative research with a descriptive approach. The data sources were selected by purposive sampling (purposed sample), the data were collected using interview techniques, observation, and documentation, analytical techniques using qualitative descriptive analysis, namely data reduction, data presentation, conclusion drawing or verification. The results of the study on the effectiveness of the use of the teacher's room application in grade VI elementary school students in improving the quality of education in the City indicate that: (1) the effectiveness of the use of this teacher's room application at the stage of observing, asking, gathering information, and communicating has not run optimally. (2) The use of the Ruang Guru application can improve the quality of education. This is proven by the process and learning tools used in this teacher's room application, all of which are up-to-date.